Efek Akupresur Dalam Mengatasi Mual Muntah Selama Kehamilan - Cucu Nurmala (JIDAN (Jurnal Ilmiah Bidan), 2022)
Background: Pregnancy is physiological. During first trimester pregnancy, 87.8% of a woman experiences nausea and vomiting, and about 90% of vomiting nausea goes away by 16 weeks of gestation. If nausea and vomiting are severe and persistent, the condition can develop into hyperemesis gravidarum. A study showed that 34% of pregnant women did not use the drug (vitamin B6) and 26% used the drug for less than the prescribed dose and they expressed a lack of confidence in the safety of the drug and preferred Complementary and Alternative Medicines (CAM). Acupressure is a type of stimulation for acupuncture with finger pressure or using the hand. Goal: to see the effect of acupressure on vomiting nausea in pregnancy. Method: This study is a literature review. Results: From a study in several studies showed that acupressure performed at the Neiguan point (Pericardium 6 / P6) by using a bracelet (wristband) continuously for 4 limits or acupressure at kidney point 21 (K1D21) diving 20 minutes per day within 4 limits can reduce vomiting nausea in pregnancy. Acupressure is no better than vitamin B6, ginger capsules are more effective than acupressure, but acupressure is more effective than acupuncture in reducing vomiting nausea in pregnancy.